Physical Literacy in Physical Education Curriculum - Bulqini, Arif; Puspodari, Puspodari; Arfanda, Poppy Elisano; Suroto, Suroto; Mutohir, Toho Cholik (Department of Physical Education, Sport, Health and Recreation, 2021)
This study discusses how Pyisical Education Teachers Educator (PETE) adopt Physical Literacy (PL). Knowledge is the foundation of PL to know what to do and when is the right time to do it. The research has a goal, so that PETE understands the definition of PL. This research study contains 3 stages, the first is determining the objectives of the PL, the second is curriculum planning and the third is the learning approach. The method used is a literature review of several opinions about PL in Physical Education (PE). The national PE curriculum is structured and developed to achieve national education goals that are adapted to current conditions and future needs in order to live regularly and actively, through Physical Activity (PA). For this reason, efforts should be made to create a healthy lifestyle and maintain physical fitness (PF). PL is a potential that can be optimally developed for children from an early age. The role of PE is very important in the formation of PL in children, where cognitive, affective and psychomotor aspects are in the goal of PE which can provide motivation, confidence and enthusiasm to continue doing PA.